Pratiche artistiche di rigenerazione urbana, integrazione culturale e trasformazione sociale attraverso il confine Messico/USA (Gilgameš, 2019)
This paper was born from a field research started in 2015 in MexicoCity, where I got to know the work of the artists presented: Torolab,Nortec Collective and Rubén Ortiz Torres.They have in common a link with the Mexico/USA border, to whichthey relate in different ways and for different reasons.The first paragraphs of the paper are meant to outline a theoreticalintroduction to the theme of the border, which is followed by astudy on the generative potential of the border areas.The central focus of the research is an excerpt of the interviewsand studio visits carried out as part of a trip undertaken in August2016, to meet the artists already mentioned and the cross-borderdynamics in person: from Tijuana (Baja California, Mexico) to LosAngeles (California, USA), walking through the border.What emerges is a portrait of the frontier region as a laboratory ofglobalization, where contrast, hybridization and cultural exchangemake innovation move faster. In this context, the work of the artistspresented demonstrates the potential of art as an engine of urbanregeneration, cultural integration and social transformation.